Stigma dan Tingkat Kecemasan Masyarakat pada Covid-19 - Lilis Banowati; Cucu Herawati; Wiwiet Indriyani (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: The increasing number of positive patients with Covid-19, the social impact in the form of stigma from being shunned by neighbors and even families and the impact of mental health, namely causing major psychosocial stresses that can trigger anxiety. Purpose  this study was to determine the stigma and level of public anxiety about Covid- 19. Methods: This type of research is descriptive quantitative, the study population is all people in the UPTD Haurgeulis Puskesmas, Indramayu Regency, as many as 88,468 people. The number of samples was 100 respondents using purposive sampling technique. Data were analyzed statistically using univariate analysis and data presentation in the form of frequency distributions. Results: This study shows that people have a low stigma as much as 1% and those who experience a high stigma are as much as 99%. As well as people who do not experience anxiety as much as 14% and most of them experience mild anxiety as much as 86%. Conclusion: The public should be wiser in sorting out information related to Covid-19 from various sources and can manage anxiety with good self-coping management, for example by relaxation and positive thinking related to Covid-19.